2001
DOI: 10.1128/jvi.75.10.4780-4791.2001
|View full text |Cite
|
Sign up to set email alerts
|

Cell-to-Cell Contact Results in a Selective Translocation of Maternal Human Immunodeficiency Virus Type 1 Quasispecies across a Trophoblastic Barrier by both Transcytosis and Infection

Abstract: Mother-to-child transmission can occur in utero, mainly intrapartum and postpartum in case of breastfeeding. In utero transmission is highly restricted and results in selection of viral variant from the mother to the child. We have developed an in vitro system that mimics the interaction between viruses, infected cells present in maternal blood, and the trophoblast, the first barrier protecting the fetus. Trophoblastic BeWo cells were grown as a tight polarized monolayer in a two-chamber system. Cell-free viri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
88
0
3

Year Published

2004
2004
2011
2011

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 93 publications
(95 citation statements)
references
References 67 publications
(74 reference statements)
4
88
0
3
Order By: Relevance
“…Several routes of entry have been proposed, including direct transcytosis through epithelial cells, infection of target cells beneath the epithelium via breaks in the lining, transepithelial transport by Langerhans cells, dendritic cells, or M cells, and transcytosis through epithelial tight junctions (1)(2)(3)(4)(5). In addition, epithelial cells derived from colon, uterus, oral cavity, and salivary gland have been reported to support HIV replication (6 -15).…”
Section: Intraepithelial Cell Neutralization Of Hiv-1 Replication By mentioning
confidence: 99%
“…Several routes of entry have been proposed, including direct transcytosis through epithelial cells, infection of target cells beneath the epithelium via breaks in the lining, transepithelial transport by Langerhans cells, dendritic cells, or M cells, and transcytosis through epithelial tight junctions (1)(2)(3)(4)(5). In addition, epithelial cells derived from colon, uterus, oral cavity, and salivary gland have been reported to support HIV replication (6 -15).…”
Section: Intraepithelial Cell Neutralization Of Hiv-1 Replication By mentioning
confidence: 99%
“…The fetus can acquire the HIV-1 as early as eight weeks of gestation (12), and infection possibly result from an alteration of the maternal-fetal barrier or an interaction of infected cells with trophoblastic cells or by HIV-1 transcytosis (15). Antiretrovirals are administered to HIV-1 positive mothers late in pregnancy; therefore, the HBDs or other antiviral soluble factors must play their protective role early in pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, reports have indicated that placental fibroblasts can act as viral reservoirs, capable of infecting other fetal cells (14). This relationship suggested avenues by which the fetus can acquire the infection by an alteration of the maternal-fetal barrier, by cell-to-cell contact from infected cells to trophoblastic cells or by HIV-1 transcytosis (15).…”
mentioning
confidence: 99%
“…L'adhérence entre les deux types cellulaires formerait une «synapse virale» pouvant favoriser l'endocytose des virions ou l'expression de molécules de surface requises pour l'entrée du VIH [26]. Enfin, l'infection est augmentée in vitro en présence d'anticorps spécifiques du VIH, et réduite en présence d'anticorps dirigés contre les galactosyl céramides, suggérant l'intervention de récepteurs Fc ou de glycolipides dans le processus de pénétration virale [22,27]. Si le mécanisme d'entrée du VIH dans les trophoblastes et les fonctions des récepteurs cellulaires restent donc sujets à débat, les données accumulées suggèrent qu'une infection des trophoblastes, par suite de leur interaction avec des virus libres ou des cellules maternelles infectées, peut apparaître au cours de la grossesse.…”
Section: Rôle Des Trophoblastesunclassified
“…Or le VIH peut être transcytosé du pôle apical au pôle basolatéral des trophoblastes, sans qu'il y ait réplication virale. Ces cellules permettraient donc le passage du VIH non pas via des microlésions, mais directement par le biais de son internalisation par les trophoblastes [27]. C'est au moyen d'un processus similaire que le VIH pourrait traverser les tissus épithéliaux de l'anus ou du vagin lors de la transmission sexuelle.…”
Section: Rôle Des Trophoblastesunclassified